2000
DOI: 10.1021/jf990745s
|View full text |Cite
|
Sign up to set email alerts
|

Critical Comparison of Three Olfactometric Methods for the Identification of the Most Potent Odorants in Cooked Mussels (Mytilus edulis)

Abstract: Three olfactometric methods (olfactometry global analysis, OSME, and AEDA) were compared to evaluate the main impact odorants of cooked mussels. The results obtained from these methods were very similar and well correlated. On the basis of the three techniques, 42 odor-active compounds were detected and 28 were identified. Among these compounds, 6 odorants seem to contribute actively to the aroma of mussels: 2,3-butanedione (4) (buttery, caramel-like odor), (Z)-4-heptenal (14) (boiled potato-like odor), (E)-2-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
87
0
4

Year Published

2006
2006
2015
2015

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 107 publications
(96 citation statements)
references
References 33 publications
4
87
0
4
Order By: Relevance
“…Trans-4-heptenal, which has been found in great quantities (Fuentes et al, 2009) and recognized as one of the most potent odorants in mussel (Le Guen et al, 2000b), is present in relatively small quantities in our mussels. Also 2,3-diones, indicated by Le Guen et al (2000aGuen et al ( , 2000b as major mussel odorants, are almost absent in our mussels but present in the fish species. The same also applies for 2,4-octadienal, that was absent from mussels in our study, but has been reported as being a major mussel odorant contributor (Le Guen et al, 2000b).…”
Section: Resultsmentioning
confidence: 97%
“…Trans-4-heptenal, which has been found in great quantities (Fuentes et al, 2009) and recognized as one of the most potent odorants in mussel (Le Guen et al, 2000b), is present in relatively small quantities in our mussels. Also 2,3-diones, indicated by Le Guen et al (2000aGuen et al ( , 2000b as major mussel odorants, are almost absent in our mussels but present in the fish species. The same also applies for 2,4-octadienal, that was absent from mussels in our study, but has been reported as being a major mussel odorant contributor (Le Guen et al, 2000b).…”
Section: Resultsmentioning
confidence: 97%
“…Detection frequency methods are usually the fastest, followed by direct-intensity methods, with dilution-based methods being the most time-consuming. The detection frequency is also the easiest method to employ, followed by dilution methods, whereas direct-intensity methods are the most complex [38].…”
Section: Comparison Of Different Gc-o Methodsmentioning
confidence: 99%
“…In theory, the method accounts for the variable sensitivities of assessors, is repeatable and the results are applicable to a population [3,32,38].…”
Section: Detection Frequencymentioning
confidence: 99%
“…The mean of odor intensity was calculated and the final odor intensities were obtained from the mean values of at least two assessors. During a 50-min sniffing period per sample, assessors ranked the intensity of each odor on a four-point intensity scale: 1 = weak, 2 = moderate, 3 = strong, and 4 = very strong [8].…”
Section: Gas Chromatography-mass Spectrometry-olfactometry (Gc-ms-o)mentioning
confidence: 99%
“…The dilution method is the dilution level at which flavor compounds cannot be smelled by the human nose [7]. The direct intensity method could offer several advantages of reducing sniffing time and errors by recording the changes of odor intensities directly, which is superior to frequency detection and the dilution method [8]. Several researchers have analyzed odor-active compounds in seafoods by GC-MS-O, such as the New Zealand sea urchin Evechinus chloroticus [9], rainbow trout Oncorhynchus mykiss [10], and Yangtze River-Coilia [11].…”
Section: Introductionmentioning
confidence: 99%